Hungarian Journal of English and American Studies (HJEAS) (JSTOR)
HJEAS (Hungarian Journal of English and American Studies--formerly HSE - Hungarian Studies of English) is devoted to literary, historical, film and cultural studies of the English-speaking world. The journal is published twice a year by the Institute of English and American Studies, University of Debrecen, Debrecen, Hungary.
Keywords: Irish Studies